Prospective and Multicenter Evaluation of Outcomes for Quality of Life and Activities of Daily Living for Balloon Kyphoplasty in the Treatment of Vertebral Compression Fractures: The EVOLVE Trial. Issue 1 (14th March 2018) - Beall, Douglas P; Chambers, M R; Thomas, Sam; Amburgy, John; Webb, James R; Goodman, Bradly S; Datta, Devin K; Easton, Richard W; Linville, Douglas; Talati, Sanjay; Tillman, John B
Abstract: BACKGROUND: Osteoporotic and neoplastic vertebral compression fractures (VCF) are common and painful, threatening quality of life and increasing risk of morbidity and mortality. Balloon kyphoplasty is a percutaneous option for treating painful cancer- and osteoporosis-related VCFs, supported by 2 randomized trials demonstrating efficacy benefits of BKP over nonsurgical care. OBJECTIVE: To investigate 12-mo disability, quality of life, and safety outcomes specifically in a Medicare-eligible population, representing characteristic patients seen in routine clinical practice. METHODS: A total of 354 patients with painful VCFs were enrolled at 24 US sites with 350 undergoing kyphoplasty. Four coprimary endpoints—Numerical Rating Scale (NRS) back pain, Oswestry Disability Index (ODI), Short Form-36 Questionnaire Physical Component Summary (SF-36v2 PCS), EuroQol-5-Domain (EQ-5D)—were evaluated for statistically significant improvement 3 mo after kyphoplasty. Data were collected at baseline, 7 d, and 1, 3, 6, and 12 mo (www.clinicaltrials.gov registration NCT01871519). RESULTS: At the 3-mo primary endpoint, NRS improved from 8.7 to 2.7 and ODI improved from 63.4 to 27.1; SF-36 PCS was 24.2 at baseline improving to 36.6, and EQ-5D improved from 0.383 to 0.746 ( P  < .001 for each). These outcomes were statistically significant at every follow-up time point. Five device-/procedure-related adverse events, intraoperative asymptomatic balloon rupture, rib pain, and aspiration pneumonia, and a new VCF 25 d postprocedure, and myocardial infarction 105 d postprocedure were reported and each resolved with proper treatment. CONCLUSION: This large, prospective, clinical study demonstrates that kyphoplasty is a safe, effective, and durable procedure for treating patients with painful VCF due to osteoporosis or cancer.